PENDAMPINGAN PEMBUATAN MODUL AJAR BIPA BERBASIS MEDIA DESAIN CANVA PADA MAHASISWA PBSI DI UNIVERSITAS MUHAMMADIYAH MAKASSAR - Hestiaty; Munirah; Ratnawati; Murni, Dewi; Seubelan, Sartiny (Education and Talent Development Center of Indonesia, 2025)
The mentoring activity in making Indonesian Language teaching modules for Foreign Speakers (BIPA) based on Canva design media aims to improve the skills of students of the Indonesian Language and Literature Education Study Program (PBSI) of Muhammadiyah University of Makassar in compiling effective and innovative teaching materials. Mentoring is carried out online through five stages, namely planning, training and practice, mentoring, evaluation, and implementation. The results of the activity show a significant increase in students' ability to design interesting and relevant BIPA teaching modules. As many as 90% of students succeeded in producing modules according to the criteria of interactive and aesthetic design. The evaluation showed that 85% of participants were satisfied with this activity. This finding confirms the importance of using Canva as a technology-based learning media to support creative and effective BIPA teaching, while introducing Indonesian culture to foreign learners.